Diversity analysis of Moroccan carob ("Ceratonia siliqua" L.) accessions using phenotypic traits and RAPD markers - Konaté, Ibrahim; Filali-Maltouf, Abdelkarim; Berraho, El Bekkay (Universidad de Málaga, Servicio de Publicaciones, 2007)
Diversity analysis of moroccan carob (Ceratonia siliqua L.) accessions using phenotypic traits and RAPD markers. The carob (Ceratonia siliqua L.) is a perennial leguminous (Caesalpinioideae) that grows as an evergreen shrub or tree. It¿s an important component of the Mediterranean vegetation and its adaptation in marginal soils of the Mediterranean regions is important environmentally and economically. Phenotypic and genetic diversity among 10 Ceratonia siliqua accessions coming from different areas of Morocco were studied with morphometric and RAPD approaches. The analysis of discriminative fruit characters showed highly significant differences among these accessions, the closely related ones have a similarity level less than 65%. No molecular studies have been carried out so far on Ceratonia siliqua. To provide markers useful for molecular diversity study of the carob tree, genomic DNA extraction and amplification conditions were finalized and 67 arbitrary primers were screened. 52 of them showed clearly reproducible banding patterns. The analysis of RAPD profiles revealed a high degree of genetic diversity within these carob accessions and enabled each of them to be uniquely fingerprinted. Overall, in our study we note that morphological relationship between carob accessions is deeply different to their molecular relationship. Concerning the distribution of the accessions according to their geographical origin, clustering based on RAPD data revealed a rough distribution of theses accessions. Indeed, Sidi Bou Ottman, Demnate and Essaouira accessions coming from the south of Morocco seem to be linked in the PCA plot. However, two geographically distant accessions, Aïn Sfa and Ouazzane coming from the north (about 700 Km) were clustered with Essaouira and Demanate - Sidi Bou Ottman, respectively.

Analyse de la diversité des accessions du caroubier marocain (Ceratonia siliqua L.) utilisant des traits phenotypiques et des marqueurs RAPD. Le caroubier (Ceratonia siliqua L.) est une légumineuse pérenne (Caesalpinioideae), à feuillage persistant et pouvant croître entant qu¿arbrisseau ou arbre. C¿est un composant important de la végétation méditerranéenne et son adaptation aux sols marginaux des régions méditerranéennes est d¿une grande importance écologique et économique. La diversité phénotypique et génétique au sein de 10 accessions de caroubier provenant de différentes régions du Maroc a été étudiée par des approches morphométriques et moléculaires (RAPD). L¿analyse des caractères morphologiques discriminants du fruit a montré des différences hautement significatives au sein des accessions, puisque les apparentées d¿entre elles n¿ont approximativement que 65% de similarité. Jusqu¿à nos jours, aucune étude moléculaire n¿a été entreprise sur Ceratonia siliqua. Pour mettre à disposition des marqueurs utiles pour l¿étude de la diversité moléculaire du caroubier, l¿extraction de l¿ADN génomique et les conditions de l¿amplification ont été mises au point et 67 amorces arbitraires ont été criblées. 52 d¿entre elles ont montré clairement des profils de bandes reproductibles. L¿analyse des profils RAPD a révélé une diversité génétique de haut niveau entre les accessions de caroubier ce qui a permis à chacune d¿elles d¿être distinguée génétiquement de façon singulière. De manière générale, nous avons noté que la relation morphologique entre les accessions du caroubier est profondément différente de leur relation moléculaire. Concernant la distribution des accessions selon leur origine géographique, le regroupement basé sur les données de la RAPD a révélé une distribution grossière. En effet, les provenances de Sidi Bou Ottman, Demnate et Essaouira, originaires du sud de Maroc, semblent être liés par l¿analyse des composantes principales (PCA). Cependant, deux accessions géographiquement distantes, Aïn Sfa et Ouazzane, originaires du Nord (approximativement 700 Kms) ont été liées avec Essaouira et Demanate - Sidi Bou Ottman, respectivement.